Od ewolucyjnych do rewolucyjnych zmian kultury organizacyjnej - Stańczyk, Sylwia (The organizational culture's changes - throughout evolution up to revolution, 2006)
Necessity of fast reaction on environment changes cause that stabilization as an organizational efficiency condition is being squeeze out. Organizational values are being formed in such conditions. Their foundation is an organizational flexibility. Flexibility is an answer for growing environment turbulences. On the other hand it calls into question views of efficiency of evolutionary culture changes. The purpose of this article is to bring above issues much closer.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1141, s. 156-162